Montgomery Multiplication in GF(2 ^k) - Koc, Cetin K.; Acar, Tolga (Designs, Codes and Cryptography, 1998)
We show that the multiplication operation c=a · b · r^-1 in the field GF(2^k) can be implemented significantly faster in software than the standard multiplication, where r is a special fixed element of the field. This operation is the finite field analogue of the Montgomery multiplication for modular multiplication of integers. We give the bit-level and word-level algorithms for computing the product, perform a thorough performance analysis, and compare the algorithm to the standard multiplication algorithm in GF(2^k). The Montgomery multiplication can be used to obtain fast software implementations of the discrete exponentiation operation, and is particularly suitable for cryptographic applications where k is large.